Analisis Pengendalian Persediaan Bahan Baku Melalui Penerapan Economic Order Quantity (EOQ) pada PT Andini Megah Sejahtera Cabang Bogor - Erma Apriyanti (Universitas Muhammadiyah Tangerang, 2017)
The purpose of this research are to learn about material inventory control in PTAndini Megah Sejahtera, to learn about inventory calculation metodh by usingEconomic Order Quantity (EOQ) metodh and to learn comparisation above totalinventory cost by total calculation of EOQ. This research approaching bydescriptive quantitattive and using data collection technique through interview,observation and librarian overview. The result of this research will describe thatmaterial inventory control in PT Andini Megah Sejahtera was not effetivebecause there is over-stock of raw material storage so that total inventorycalculation were high. Therefore, by using EOQ metodh total calculation of theinventory are lower than before using EOQ metodh.Keyword : Inventory, Raw material,and Economic Order Quantity